EFEKTIFITAS TERAPI ASSERTIVE TRAINING TERHADAP KEMAMPUAN KOMUNIKASI ASERTIF DAN SELF ESTEEM PADA REMAJA DENGAN PERILAKU AGRESIF - Rista Nora; Marizki Putri (STIKes Al-Insyirah Pekanbaru, 2022)
Communication is the basis of all social interaction activities in everyday life. The purpose of communication is to convey desires and feelings to others, where in conveying desires and feelings it should be important to keep paying attention to the rights of others or what is called assertive communication. The lack of ability of adolescents in assertive communication causes the high incidence of aggressive behavior in adolescents and makes adolescents' self-esteem negative. Assertive communication skills can be improved by providing Assertiveness Training group therapy.In the last three years, there has been an increase in the incidence of aggressive behavior both in adolescents and in school-age children, where this increase occurs 40% every year. Aggressive behavior is a form of individual emotional expression due to an unsuccessful experience. The purpose of this study was to see the effectiveness of assertive training therapy on assertive communication skills and self-steem in adolescents with assertive behavior. This type of research is a quasi-experimental approach with